2021
DOI: 10.1007/s00436-021-07113-y
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and tolerability of a squalane and dimethicone-based treatment for head lice

Abstract: Head lice (Pediculus humanus capitis) are worldwide obligate human ectoparasites, with high implications in pediatrics. In Europe, first-line topical neurotoxic insecticidal therapeutic strategies are being replaced by topical physically acting agents as the first-choice treatment. Safety of the active ingredients and high efficacy in a one-time single-dose treatment with a brief treatment application time are key issues for consumer use and effective compliance. The aim of this study was to assess the in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…The prevalence of pediculosis has been reported to be growing worldwide since the mid-1960s reaching up to 80% in some countries (9). However, based on epidemiological studies, the average prevalence rate of pediculosis in schools in different countries was stated to be 16%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of pediculosis has been reported to be growing worldwide since the mid-1960s reaching up to 80% in some countries (9). However, based on epidemiological studies, the average prevalence rate of pediculosis in schools in different countries was stated to be 16%.…”
Section: Discussionmentioning
confidence: 99%
“…As an illness, pediculosis comes second after the common cold among schoolchildren worldwide with infection rates ranging between 5% in Europe and 33% in South America (7,8). In Iran, head louse infestation is a common health problem, although, the prevalence of pediculosis varies in different regions from 0.9 to 20.5% (9)(10)(11)(12). Studies have shown that public centers such as barracks, dormitories, educational centers, and communities are the most infected locations in Iran (1).…”
Section: Introductionmentioning
confidence: 99%
“…A study in 2021 designed a squalane and dimethicone-based formula for treating head lice. The results indicated that the formula was safe for children with good skin compatibility and acceptability [25].…”
Section: Synthetic Emollientsmentioning
confidence: 92%
“…Squalene, phytol, and phytol acetate were identified in H. persicum, underscoring a more diverse terpene profile compared to H. aphyllum. The literature supports that both phytol and its derivatives [104][105][106], as well as squalene [107][108][109], exhibit marked insecticidal properties. These terpenes are present in the metabolic spectrum of the control H. persicum but absent in H. aphyllum.…”
Section: Terpenoidsmentioning
confidence: 96%